2004
DOI: 10.1074/jbc.m406028200
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomal Proliferator-activated Receptor-γ Coactivator-1α (PGC-1α) Enhances the Thyroid Hormone Induction of Carnitine Palmitoyltransferase I (CPT-Iα)

Abstract: Carnitine palmitoyltransferase I (CPT-I) catalyzes the rate-controlling step in the pathway of mitochondrial fatty acid oxidation. Thyroid hormone will stimulate the expression of the liver isoform of CPT-I (CPT-I␣). This induction of CPT-I␣ gene expression requires the thyroid hormone response element in the promoter and sequences within the first intron. The peroxisomal proliferator-activated receptor-␥ coactivator-1␣ (PGC-1␣) is a coactivator that promotes mitochondrial biogenesis, mitochondrial fatty acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 38 publications
5
89
1
1
Order By: Relevance
“…It was found that addition of T 3 to human peripheral blood mononuclear cells increased the abundance of SIRT1 after 24 h (41). We tested whether T 3 would increase SIRT1 abundance in the liver since other nuclear factors such as PGC-1␣ and C/EBP␤ are induced by T 3 (7,42). We did not observe any elevation of SIRT1 abundance by T 3 in rat hepatocytes (Fig.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…It was found that addition of T 3 to human peripheral blood mononuclear cells increased the abundance of SIRT1 after 24 h (41). We tested whether T 3 would increase SIRT1 abundance in the liver since other nuclear factors such as PGC-1␣ and C/EBP␤ are induced by T 3 (7,42). We did not observe any elevation of SIRT1 abundance by T 3 in rat hepatocytes (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…As these genes are often T 3 targets, we speculated that SIRT1 and T 3 might co-regulate gene expression. We previously reported that PGC-1␣ participates in the T 3 induction of several hepatic genes (6,7). PGC-1␣ is activated by SIRT1 via the deacetylation of multiple lysines suggesting that SIRT1 might enhance the T 3 induction via activation of PGC-1␣ (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These co-factors may be stimulated (or not) according to specific physiopathological situations and/or the tissues in question. For instance, liver PGC1A enhances the stimulatory action of thyroid hormone on CPT1 [37]. If the same mechanism regulates muscle CPT1, the well documented decrease of thyroid function during active weight loss process [38] could conceivably prevent an increase of CPT1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…3B). We quantified the mRNA level of the ␤-oxidation related genes PPAR␣ (23,24), CPT-1a (25,26), and ACO (27) in the liver using qRT-PCR. The mRNA expression level of PPAR␣ in the P group tended to be lower than that of the R group (pϭ0.09 vs. P), showing that dietary supplementation with Lys tended to increase PPAR␣ mRNA levels (Fig.…”
Section: Pgc-1␣ and Genes Related To ␤-Oxidation In The Liver Of Sampmentioning
confidence: 99%